2020
DOI: 10.4062/biomolther.2019.201
|View full text |Cite
|
Sign up to set email alerts
|

Econazole Induces p53-Dependent Apoptosis and Decreases Metastasis Ability in Gastric Cancer Cells

Abstract: Econazole, a potent broad-spectrum antifungal agent and a Ca 2+ channel antagonist, induces cytotoxicity in leukemia cells and is used for the treatment of skin infections. However, little is known about its cytotoxic effects on solid tumor cells. Here, we investigated the molecular mechanism underlying econazole-induced toxicity in vitro and evaluated its regulatory effect on the metastasis of gastric cancer cells. Using the gastric cancer cell lines AGS and SNU1 expressing wild-type p53 we demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The current data are consistent with Dong and his colleagues' study that showed that econazole (Imidazole derivative) induces apoptosis in lung cancer cells through the PI3K/AKT signaling pathways. Hence, their data represented that p-AKT and p-PI3K expression levels were downregulated entirely by econazole [46]. This in agreement with a previous study that reported PI3K inhibitors combinations with doxorubicin exhibit better efficacy than monotherapy due to their strong synergistic antiproliferative effect of those combinations, via inducing PI3K/AKT signaling blockage, which in turn led to activate caspase-3/7 and caspase-9 and changed the expression of several apoptosis-related gene expression [47].…”
Section: Dual Inhibition Of Autophagic Flux and Pi3k/akt Pathway-depesupporting
confidence: 89%
“…The current data are consistent with Dong and his colleagues' study that showed that econazole (Imidazole derivative) induces apoptosis in lung cancer cells through the PI3K/AKT signaling pathways. Hence, their data represented that p-AKT and p-PI3K expression levels were downregulated entirely by econazole [46]. This in agreement with a previous study that reported PI3K inhibitors combinations with doxorubicin exhibit better efficacy than monotherapy due to their strong synergistic antiproliferative effect of those combinations, via inducing PI3K/AKT signaling blockage, which in turn led to activate caspase-3/7 and caspase-9 and changed the expression of several apoptosis-related gene expression [47].…”
Section: Dual Inhibition Of Autophagic Flux and Pi3k/akt Pathway-depesupporting
confidence: 89%
“…Anisomycin can inhibit angiogenesis, proliferation and invasion of tumor cells by blocking the PI3K/Akt pathway ( Ushijima et al, 2021 )and Notch1 pathway ( Ye et al, 2019 ). Econazole induces cell apoptosis and inhibits cancer invasion through the elevated protein level of p53 ( Choi et al, 2020 ). Imatinib reduces the phosphorylation of the PDGFRα/Akt axis, suppressing tumor cell growth and migration ( Nayeem et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Invasion assays were performed using transwells that were coated with Matrigel (0.5 μg/mL) (Neuro Probe Inc., Gaithersburg, MD) following a previous report ( Choi et al ., 2020 ). Coat Matrigel (10 μL/well) in the transwell insert, overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%